Design and performance of a toroidal radiofrequency volume coil with intrinsic electromagnetic interference rejection for low‐field portable Halbach‐based MRI systems - Vliem, Jules; Najac, Chloe; Lena, Beatrice; Webb, Andrew; Zivkovic, Irena (Magnetic resonance in medicine, 2025)
One of the intrinsic limitations of low-field MRI is low signal-to-noise ratio, which can be further reduced by electromagnetic interference (EMI) due to the lack of a Faraday shielded room. To address this issue, we propose a novel radiofrequency (RF) coil design that is inherently less sensitive to EMI while maintaining high receive sensitivity. The proposed coil structure is based on an anapole (toroidal) design and consists of six rings, each containing four continuous wires wound around an elliptical three-dimensional-printed former. The wire in the entire structure is uninterrupted. This coil is designed for use in systems with an axial B field direction. The performance of the proposed RF coil was evaluated on a Halbach array system designed for neuroimaging and operating at 47 mT and compared with a widely used spiral head coil. The noise level achieved by the proposed toroidal coil in combination with a belt wrapped around the subjects and grounded to the scanner was comparable to that of the widely used spiral head coil when combined with a grounding belt and passive aluminum shielding. The coil transmit and receive efficiency was comparable to the efficiency of the spiral head coil. The proposed RF coil inherently reduces the effect of EMI, potentially removing or reducing the need for passive shielding or external/internal sensors for EMI reduction in postprocessing.